Sociobehavioural factors associated with SARS-CoV-2 infection and COVID-19 vaccine effectiveness against medically attended, symptomatic SARS-CoV-2 infection in the Philippines: a prospective case-control study (FASCINATE-P study) - Arashiro, Takeshi; Berba, Regina Pascua; Calayo, Joy Potenciano; Kris, Marie; Garcia, Reby Marie; Suzuki, Shuichi; Dungog, Cecile; Rivera, Jonathan; Malijan, Greco Mark; Agrupis, Kristal An; Salazar, Mary Jane; Salazar, Mary Ann; et al. (Western Pacific Surveillance and Response, 2025)
Objective: We examined sociobehavioural factors associated with SARS-CoV-2 infection and estimated COVID-19 vaccine effectiveness against symptomatic SARS-CoV-2 infection in the Philippines. Such studies are limited in low- and middle-income countries, especially in Asia and the Pacific. Methods: A case-control study was conducted in two hospitals in Manila, Philippines, from March 2022 to June 2023. Sociobehavioural factors and vaccination history were collected. PCR-positive individuals were cases, while PCR-negative individuals were controls. Adjusted odds ratios (aORs) were calculated to examine associations between sociobehavioural factors/vaccination and medically attended SARS-CoV-2 infection. Results: The analysis included 2489 individuals (574 positive cases, 23.1%; 1915 controls, 76.9%; median age [interquartile range]: 35 [27–51] years). Although education and household income were not associated with infection, being a health-care worker was (aOR: 1.45; 95% confidence interval [CI]: 1.03–2.06). The odds of infection were higher among individuals who attended gatherings of five or more people compared to those who attended smaller gatherings (aOR: 2.58; 95% CI: 1.14–5.83). Absolute vaccine effectiveness for vaccination status was not estimated due to a high risk of bias, for example, unascertained prior infection. Moderate relative vaccine effectiveness for the first booster (32%; 95% CI: -120–79) and the second booster (48%; 95% CI: -23–78) were observed (both with wide CI), albeit with a waning trend after half a year. Discussion: The higher odds of infection among health-care workers emphasize the importance of infection prevention and control measures. Moderate relative vaccine effectiveness with a waning trend reiterates the need for more efficacious vaccines against symptomatic infection caused by circulating variants and with longer duration of protection.